Lipoic Acid Attenuates Inflammation via cAMP and Protein Kinase A Signaling - Salinthone, Sonemany; Yadav, Vijayshree; Schillace, Robynn V.; Bourdette, Dennis N.; Carr, Daniel W. (PloS one, 2010)
Abnormal regulation of the inflammatory response is an important component of diseases such as diabetes, Alzheimer's disease and multiple sclerosis (MS). Lipoic acid (LA) has been shown to have antioxidant and anti-inflammatory properties and is being pursued as a therapy for these diseases. We first reported that LA stimulates cAMP production via activation of G-protein coupled receptors and adenylyl cyclases. LA also suppressed NK cell activation and cytotoxicity. In this study we present evidence supporting the hypothesis that the anti-inflammatory properties of LA are mediated by the cAMP/PKA signaling cascade. Additionally, we show that LA oral administration elevates cAMP levels in MS subjects. We determined the effects of LA on IL-6, IL-17 and IL-10 secretion using ELISAs. Treatment with 50 µg/ml and 100 µg/ml LA significantly reduced IL-6 levels by 19 and 34%, respectively, in T cell enriched PBMCs. IL-17 levels were also reduced by 35 and 50%, respectively. Though not significant, LA appeared to have a biphasic effect on IL-10 production. Thymidine incorporation studies showed LA inhibited T cell proliferation by 90%. T-cell activation was reduced by 50% as measured by IL-2 secretion. Western blot analysis showed that LA treatment increased phosphorylation of Lck, a downstream effector of protein kinase A. Pretreatment with a peptide inhibitor of PKA, PKI, blocked LA inhibition of IL-2 and IFN gamma production, indicating that PKA mediates these responses. Oral administration of 1200 mg LA to MS subjects resulted in increased cAMP levels in PBMCs four hours after ingestion. Average cAMP levels in 20 subjects were 43% higher than baseline. Oral administration of LA in vivo resulted in significant increases in cAMP concentration. The anti-inflammatory effects of LA are mediated in part by the cAMP/PKA signaling cascade. These novel findings enhance our understanding of the mechanisms of action of LA.